2011
DOI: 10.1166/jnn.2011.3625
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Films as a Novel Substrate for Chondrocytes Growth

Abstract: We fabricated a large area silica nano-particle monolayer on glass substrates for the cell growth by the Langmuir-Blodgett technique. A thin film of 300 nm sized mono-dispersed silica particles was constructed on the air-water interface and transferred onto a glass substrate. Chondrocytes were cultured on nano-structured substrates and bare glass substrates for 8 days. The characterizations of chondrocytes on nano-structured substrate were conducted on 3rd and 6th day using confocal laser microscopy and with M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, because the silica substrates reported to date have relatively limited biocompatibility, there is a lack of understanding of the cellular responses of mammalian cells to growth on silica substrates [ 14 , 15 ]. In previous studies, our group fabricated silica nanostructured substrates (SN) on glass using the LB technique, demonstrating that this approach provides a simple method for producing uniform and reproducible SN with nanoscale level roughness [ 16 , 17 , 18 ]. We also examined SN as culture substrates for chondrocytes and observed that SN promoted good adhesion and proliferation without promoting dedifferentiation and thus served as adaptable culture substrates for chondrocytes [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because the silica substrates reported to date have relatively limited biocompatibility, there is a lack of understanding of the cellular responses of mammalian cells to growth on silica substrates [ 14 , 15 ]. In previous studies, our group fabricated silica nanostructured substrates (SN) on glass using the LB technique, demonstrating that this approach provides a simple method for producing uniform and reproducible SN with nanoscale level roughness [ 16 , 17 , 18 ]. We also examined SN as culture substrates for chondrocytes and observed that SN promoted good adhesion and proliferation without promoting dedifferentiation and thus served as adaptable culture substrates for chondrocytes [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, our group fabricated silica nanostructured substrates (SN) on glass using the LB technique, demonstrating that this approach provides a simple method for producing uniform and reproducible SN with nanoscale level roughness [ 16 , 17 , 18 ]. We also examined SN as culture substrates for chondrocytes and observed that SN promoted good adhesion and proliferation without promoting dedifferentiation and thus served as adaptable culture substrates for chondrocytes [ 18 ]. Although chondrocytes were found to adhere, spread, and proliferate on SN, additional detailed studies of cellular responses of other mammalian cells grown on SN are needed.…”
Section: Introductionmentioning
confidence: 99%